Technological surveillance and competitive intelligence in the business model of the Colombian hotel sector - Moya-Espinosa, Pedro Ignacio; Moscoso-Durán, Fabio Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article emphasizes the concepts of Technological Vigilance, TV, and Competitive Intelligence, CI, in order to establish their importance for hotel companies and the role they play in the economic development of Colombia. It was based on a theoretical-conceptual review of the following topics: Tourism and Hotel Industry, Globalization, Competitiveness and VT and CI. Finally, a proposal is made that aims to motivate the application of the tools of VT and IT to look for a better level of business performance in the Colombian hotel sector.